Reciprocating thermocapillary plug motion in an externally heated capillary - Jiao, Zhenjun (2012)
This paper reports the concept and experimental results of reciprocating thermocapillary motion of a liquid plug in microchannels. This paper first describes a one-dimensional analytical model for the transport of microplugs in a capillary. The model considers the coupling effect between heat transfer in the capillary wall and the surface tension driven movement of the plug. Because surface tension depends on temperature, the transient temperature distribution determines the surface tension difference across a plug and thus its movement. In the experiments, we used two heaters, which were activated alternatively. The liquid plug was positioned between the two heaters. The periodic temperature gradients generated by the two heaters made the liquid plug to move back and forth. The position of the plugs was captured and evaluated using a CCD camera. This paper presents the results of this motion with different switching frequencies, viscosities and plug sizes. This actuation concept has potential applications in postprocessing stages for droplet-based microfluidics.